Faktor-Faktor yang Berhubungan dengan Kejadian KEK pada Ibu Hamil di Puskesmas Ciwaringin - ulfah, vina ulfah vina; Yuswati; Rafika, Muhana; Bonita, Ika Amalia (NUTRITURE JOURNAL, 2026)
Background: Chronic Energy Deficiency is a condition in which a pregnant woman experiences long-term nutritional deficiency, one of which is indicated by a mid–upper arm circumference (MUAC) of < 23.5 cm. This condition may be influenced by several factors, including infectious diseases, income, education level, maternal age, interpregnancy interval, parity, and antenatal care visits. Objective: This study aimed to identify the factors associated with the occurrence of Chronic Energy Deficiency among pregnant women. Methods: This study employed a quantitative research method with a case–control design and a retrospective approach. The study subjects consisted of 100 pregnant women, including 50 respondents in the case group and 50 respondents in the control group. The sampling technique used was purposive sampling. The research instrument was a questionnaire covering infectious diseases, income, education level, maternal age, interpregnancy interval, parity, and antenatal care visits. Data Analysis: Data were analyzed using the Chi-square test. Results: The results of the chi-square test showed that infectious diseases (p = 1.000), income (p = 1.000), education level (p = 0.212), maternal age (p = 1.000), parity (p = 0.435), and the number of antenatal care visits (p = 0.635) were not associated with the occurrence of CED. However, the interpregnancy interval (p = 0.025) was significantly associated with the occurrence of CED. Conclusion: The interpregnancy interval showed a significant association with Chronic Energy Deficiency, while infectious diseases, income, education level, maternal age, parity, and antenatal care visits were not significantly associated with the occurrence of CED among pregnant women.